PENCEMARAN LINGKUNGAN PERAIRAN SUNGAI SALAH SATU FAKTOR PENYEBAB BANJIR DI JAKARTA - Susmarkanto, Susmarkanto (Jurnal Teknologi Lingkungan, 2002)
Flood is a natural dissaster that causes a lot of people suffer severely in most places of Jakarta, flood occurs yearly. Many factors effect this devastating dissasters one of which is caused by environment pollution of rivers. Main pollution comes from industrial and domestic waste. The contents of the waste continously couse river shallow and discarasing its wide. River shallow often causes flooding become river capasity in storing and flowing precipitation to the sea is decreasing. This paper assess the background of social cultural Behavior people that dispose their waste in river. The concept of river as the place for their waste and dirts has been their habit and value system on the urban and city. The bad habit causes river loose its function.